IMPROVED TECHNIQUES FOR STABLE ISOTOPE ANALYSES OF MICROLITRE QUANTITIES OF WATER FROM FLUID INCLUSIONS IN HALITE AND CONCENTRATED BRINES - Wenbo Y.; Krouse H.R.; Spencer R.J. (My University, 1996)
A method has been developed to analyze both H- and O-isotope compositions of saline waters and fluid inclusion brines without significant interference of salts. It involves high-temperature distillation under vacuum and reaction of the extracted water with zinc to produce H2 for H-isotope analyses and with guanidine hydrochloride (GuHCl) to produce CO2 for O-isotope analyses. Precisions of +/-2%% and +/-0.3%% for δD- and δ18O-values, respectively, can be realized with as little as 4 μl saline water for both elements.